ANALYSIS OF THE FACTORS CAUSING BAD CREDIT AT SHARIA COMMERCIAL BANKS IN INDONESIA - Siti Nurhayati Nafsiah; liano, Arlon (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
This purpose of this study was to analyze the factors that cause bad debts at Islamic commercial banks in Indonesia. The population in this study is Islamic Commercial Banks registered with the Financial Services Authority (OJK). Samples were taken through saturated sampling techniques totaling 13 Islamic Commercial Bank data in Indonesia. Factors causing bad debts at Islamic Commercial Banks in Indonesia are shown through reports and data that have been registered with the Financial Services Authority (OJK). The factors that cause bad credit are very important to study because the magnitude of the problems that occur within the internal company is caused by bad credit. The results of this study indicate that based on the t test the BOPO variable (Operating Costs of Operating Income) has a significant effect on NPF (Non Perfotming Financing), Likewise the FDR variable (Financing to Deposit Ratio) has a significant effect on NPF (Non Perfoming Financing). Then in the F test it is known that the BOPO and FDR variables have a significant effect on NPF. The conclusion shows that both partially and simultaneously the BOPO and FDR variables affect NPF